Functional composite filler, flame-retardant antistatic soft polyvinyl chloride composite material and preparation method

By dispersing the conductive filler in the soft PVC material into the flake filler matrix, and utilizing the bridging effect of the additional conductive filler, conductive percolation inside the composite material is achieved, which solves the problem of mechanical performance of traditional soft PVC materials in the coal mining field. In order to solve the problems of poor flame retardancy, insufficient flame retardancy and easy generation of static sparks, composite materials with low resistivity, excellent mechanical properties and good flame retardant properties have been obtained.

CN119350711APending Publication Date: 2025-01-24山西保海管业有限责任公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411543330.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional soft PVC materials have problems such as poor mechanical properties, low temperatures are prone to brittleness, insufficient flame retardancy, and easy to produce electrostatic sparks in applications in coal mine gas extraction and ventilation. In addition, conventional conductive fillers are difficult to disperse well, resulting in material conductivity. Not much increase, high cost.

Method used

By dispersing the conductive fillers in an easy -to -disperse chip -shaped filler matrix, prepare the function of composite fillers, and the internal conductivity inside the composite material is excessive and reduced the resistivity of the composite material to reduce the resistivity.

Benefits of technology

Under the low -purpose conductive filler, a soft PVC composite material obtained low resistivity, excellent mechanical performance and good flame retardant performance meet the standards of flame retardant and anti -static performance of the Ministry of Coal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350711A_ABST
    Figure CN119350711A_ABST
Patent Text Reader

Abstract

The invention discloses a functional composite filler, a flame-retardant antistatic soft polyvinyl chloride composite material and a preparation method, and belongs to the technical field of polyvinyl chloride composite materials. The functional composite filler comprises the following raw materials: Na-montmorillonite, a surfactant and a conductive filler; the polyvinyl chloride composite material comprises the following raw materials: polyvinyl chloride, a functional composite filler, a stabilizer, a conductive filler, a plasticizer and the like. The conductive filler is dispersed in the flaky filler matrix which is easy to disperse to prepare the functional composite filler, the dispersion of the conductive filler is driven by the dispersion of the matrix filler, and then the conductive percolation in the composite material is realized under the bridging action of a small amount of externally added conductive filler, so that the resistivity of the material is rapidly reduced to 106ohm or below; therefore, the soft PVC composite material with low resistivity, excellent mechanical property and good flame retardant property can be obtained under the condition of low dosage of conductive filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyvinyl chloride (PVC) composite materials, and relates to a functional composite filler, a flame-retardant and antistatic soft polyvinyl chloride composite material and a preparation method thereof. Background Art

[0002] Traditional PVC is widely used in the field of water supply and drainage, and has certain advantages such as acid resistance, alkali resistance, corrosion resistance, and ability to withstand internal pressure. However, traditional PVC has poor mechanical and mechanical properties, is not anti-static, easily becomes brittle at low temperatures, is not flame retardant enough, produces smoke when burned, is not resistant to aging, and is prone to static sparks. These defects are not conducive to the application of PVC materials in coal mine fields such as coal mine gas extraction and ventilation.

[0003] First, PVC can be divided into three categories: soft, hard and semi-hard, according to the amount of plasticizer added. As the utilization rate of soft PVC increases year by year, its application field is getting wider and wider. However, because a large amount of plasticizer is added to soft PVC during the processing, although the processing performance and plasticity of PVC are improved to a certain extent, the hardness of PVC is reduced, and the flame retardant and mechanical properties of soft PVC are seriously affected. During the combustion process of soft PVC, a large amount of thick smoke will be generated, which is very likely to cause secondary damage, seriously endangering people's life and property safety, and destroying the green environment on which people depend for survival. These have greatly reduced the safety of soft PVC in application; secondly, in order to achieve the antistatic performance requirements of soft PVC, the conventional method is to add a large amount of conductive filler to the matrix PVC material, but the conductive filler agglomerates due to the strong π-π interaction and van der Waals coupling between particles, and cannot be well dispersed in the PVC matrix. Therefore, while causing the PVC material to become hard and brittle, the conductivity does not increase much. At the same time, the addition of a large amount of conductive filler significantly increases the cost of the material, which cannot meet the requirements of industrial production. Summary of the invention

[0004] The present invention overcomes the shortcomings of the prior art and provides a functional composite filler, a flame retardant and antistatic soft polyvinyl chloride composite material and a preparation method thereof; firstly, a conductive filler is dispersed in an easily dispersed flaky filler matrix to prepare a functional composite filler, and the dispersion of the matrix filler drives the good dispersion of the loaded conductive filler, and then, under the bridging effect of a small amount of external conductive filler, the conductive percolation inside the composite material is realized, so that the resistivity of the material is rapidly reduced to 10 6 The filler is well dispersed in the plasticized PVC matrix, which makes the material have excellent mechanical properties and good flame retardant properties.

[0005] The present invention is achieved through the following technical solutions: A functional composite filler comprises the following raw materials in the following mass ratio: 16-20 parts of sodium-based montmorillonite; 3-8 parts of surfactant; and 2-6 parts of conductive filler.

[0006] Preferably, the surfactant is one or a combination of two of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, dodecyltrimethylammonium bromide, and dioctadecyldimethylammonium chloride.

[0007] Preferably, the conductive filler is one of special conductive carbon black, conductive graphite powder, carbon nanotubes, or a combination of two thereof.

[0008] A method for preparing a functional composite filler comprises the following steps: S1. Swelling sodium-based montmorillonite to obtain a montmorillonite suspension; adding a surfactant to the montmorillonite suspension, adding anhydrous ethanol, and then vigorously stirring at 60-80° C. for 1-3 hours; separating and drying to obtain modified montmorillonite; the modified montmorillonite has a particle size range of 0.5-5 μm; S2. Add the obtained modified montmorillonite and conductive filler into acetone, disperse them under ultrasonic conditions for 1-2 hours, fully dry and crush them to a product particle size range of 0.5-5 μm, and obtain a functional composite filler loaded with a conductive filler.

[0009] Furthermore, the swelling is performed by dispersing sodium montmorillonite in deionized water to obtain a suspension, and then fully stirring the suspension at room temperature to obtain swollen montmorillonite; the mass ratio of sodium montmorillonite to deionized water is 1 / 10 to 2 / 10, and the ratio of anhydrous ethanol to deionized water is 1 / 1 to 4 / 1.

[0010] A flame-retardant and antistatic soft polyvinyl chloride composite material comprises the following raw material components in weight ratio: 90-120 parts of polyvinyl chloride; 1-5 parts of a stabilizer; 50-65 parts of a plasticizer; 1-5 parts of a flame retardant; 1-5 parts of a lubricant; 15-33 parts of the functional composite filler; and 0-3 parts of a conductive filler.

[0011] Preferably, the stabilizer is one or any combination of a lead salt stabilizer, calcium stearate, lead stearate or a rare earth composite stabilizer.

[0012] Preferably, the plasticizer is one or any combination of dioctyl phthalate, dibutyl phthalate, dioctyl adipate or pentaerythritol oleate.

[0013] Preferably, the lubricant is one or any combination of chlorinated polyethylene wax, paraffin, stearic acid or polyethylene wax; the flame retardant is one or any combination of antimony trioxide, antimony pentoxide and decabromodiphenyl ether.

[0014] A method for preparing a flame-retardant and antistatic soft polyvinyl chloride composite material comprises the following steps: S1. After weighing polyvinyl chloride, stabilizer, lubricant, flame retardant and functional composite filler according to weight, stir at high speed to mix thoroughly; when stirring until the material temperature reaches 86-90°C, add plasticizer, continue stirring at high speed until the material temperature reaches 100-120°C, and then switch to low-speed stirring; transfer the material to a mixer with cooling function, continue mixing and stirring at low temperature in the mixer, cool it to 40-60°C, and obtain a mixed material; the speed of the high-speed stirring is 1000-1500rpm / min; S2. The mixed material obtained in S1 is extruded by a twin-screw extruder, and granulation is performed by traction air cooling, with the ratio of the discharge rate to the drawing rate being 1 / 1.5 to 1 / 3; the processing temperature of the twin-screw is controlled within the range of 130 to 170° C., and the granules are fully cooled to obtain a composite material.

[0015] The beneficial effects of the present invention compared with the prior art are as follows: The soft PVC composite material of the present invention disperses the conductive filler in an easily dispersed flaky filler matrix to prepare a functional composite filler. The dispersion of the conductive filler is driven by the dispersion of the matrix filler, and then the conductive percolation inside the composite material is realized under the bridging effect of a small amount of external conductive filler, so that the resistivity of the material is rapidly reduced to 10 6 Ω or less; thus, a soft PVC composite material with low resistivity, excellent mechanical properties and good flame retardant properties can be obtained with a low amount of conductive filler.

[0016] By using functional composite fillers instead of conventional conductive fillers, the surface resistivity of the composite material can be reduced to less than 1*10 6 The composite material has good flame retardancy and mechanical properties. In terms of flame retardancy, both flame combustion and flameless combustion meet the MT181-1988 standard; in terms of mechanical properties, the tensile strength can reach 19.8MPa and the elongation at break is ≥160%. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 are scanning electron microscope photos of montmorillonite; wherein (a) is pure sodium-based montmorillonite, and (b) is the modified montmorillonite prepared in Example 1; Figure 2 are scanning electron microscope photos of functional composite fillers; (c) is Example 1; (d) is Example 2; (e) is Example 3; (f) is Example 4; Figure 3 The following are scanning electron microscope photos of the cross-sections of the soft PVC composite materials obtained in Example 5 and the comparative example; DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.

[0019] Examples 1, 2, 3, and 4 provide a specific preparation method for a functional composite filler. The raw materials and proportions used are shown in Table 1. The specific preparation method is as follows: S1. Disperse sodium montmorillonite in deionized water to obtain a suspension, and then fully stir the suspension at room temperature for 24 hours to obtain swollen sodium montmorillonite. Then slowly add dioctadecyl dimethyl ammonium chloride to the sodium montmorillonite suspension, and then add anhydrous ethanol, and then vigorously stir at 80°C for 3 hours. Finally, the product is obtained by centrifugal separation. After the product is fully dried, it is crushed by high-pressure airflow mill to obtain modified montmorillonite.

[0020] S2. Add the obtained modified montmorillonite and carbon nanotubes into acetone, disperse them under ultrasonic conditions for 2 hours, and grind them with a high-pressure air flow mill after being fully dried to obtain a functional composite filler loaded with a conductive filler.

[0021] The above-mentioned vigorous stirring adopts a high-speed stirrer, and the rotation speed of the stirrer is 1000rpm / min.

[0022] The scanning electron microscope images of the sodium-based montmorillonite involved in Examples 1-4 and the modified montmorillonite in Example 1 are as follows: Figure 1 The scanning electron microscope images of the functional composite fillers prepared in Examples 1-4 are shown in FIG. Figure 2 shown.

[0023] from Figure 1 It can be seen that the untreated sodium-based montmorillonite (Figure a) is aggregated into a mass with a size of about 8~10μm. After surface organic modification, the sodium-based montmorillonite is separated into a lamellar structure (Figure b). After further compounding with carbon nanotubes, see Figure 2 (Figures c, d, e, f), the carbon nanotubes are well intercalated between the montmorillonite layers, and with the increase in the amount of surface modifier dioctadecyldimethylammonium chloride and carbon nanotubes, the degree of exfoliation between the montmorillonite layers increases, and the amount of carbon nanotubes doped between the layers also increases.

[0024] Examples 5, 6, 7, 8 and the comparative example propose a specific preparation method of a flame retardant and antistatic soft PVC composite material filled with a functional composite filler. The raw materials and proportions used are shown in Table 2. The functional composite fillers used are all prepared by Example 4.

[0025] Examples 5 to 8 and the comparative example were prepared using the following preparation process: Step 1. According to Table 2, the required mass of polyvinyl chloride, lead stearate, calcium stearate, functional composite filler, carbon nanotubes, microcrystalline wax, stearic acid and antimony trioxide are weighed and added into a high-speed mixer, and stirred at high speed (speed 1500 rpm / min) to mix them completely; when the material temperature reaches 80°C, dibutyl phthalate and dioctyl phthalate are added according to the amounts in Table 2, and high-speed stirring is continued until the material temperature reaches 110°C, and then low-speed stirring is switched (speed 500 rpm / min); the material is transferred to a mixer with a cooling function, and the mixing and stirring is continued in the mixer to cool it to 50°C to obtain a mixed material.

[0026] Step 2: The mixture obtained in step 1 is extruded by a twin-screw extruder, and granulation is performed by traction air cooling, and the ratio of the discharge rate to the drafting rate is set to 1 / 2. The temperatures of the 6 processing zones of the twin-screw are respectively controlled as follows: 140°C in zone 1, 145°C in zone 2, 150°C in zone 3, 160°C in zone 4, 170°C in zone 5, and 175°C in zone 6. After the pellets are fully cooled, a composite material is obtained.

[0027] The obtained composite material was processed into a φ50 hose. After the hose was fully cooled, a ring with a width of 30 mm was cut from the hose, and then various parameter tests as listed in Table 3 were performed.

[0028] As can be seen from Table 3, the flame retardant and antistatic soft polyvinyl chloride (PVC) composite material of the present invention, after adding functional composite fillers, can achieve the surface resistivity of the comparative example without adding functional composite fillers by adding 120g of carbon nanotubes at a PVC matrix dosage of 1000g. As the content of the added carbon nanotubes increases, the resistivity of the composite material decreases significantly. This is because the added carbon nanotubes act as a conductive bridging medium to connect the functional composite fillers and provide a path for electron migration. In the traditional comparative example, although the carbon nanotube filler is very high (reaching 120g / 1000gPVC), the carbon nanotubes cannot be well dispersed in the matrix and cannot play a good conductive bridging role, so the resistivity is not effectively reduced.

[0029] The cross-sectional scanning electron microscope photos of the composite materials of Example 5 and Comparative Example are as follows: Figure 3As shown in the figure, it can be seen that the carbon nanotubes added into the PVC matrix as functional composite fillers are dispersed very evenly in the PVC, and individual carbon nanotubes are pulled out in the cross section. In the cross section of the comparative example, the carbon nanotubes still exist in the form of clusters.

[0030] It can also be seen from Table 3 that the mechanical strength of the PVC composite material prepared by the embodiment of adding the functional composite filler is greatly improved, and its tensile strength is increased from 11.8 MPa of the comparative example to 19.8 MPa, the elongation at break is not greatly reduced, and the hardness is significantly reduced, which provides a guarantee for the use of the material in low temperatures in winter.

[0031] In summary, the flame retardant and antistatic soft PVC composite material prepared by the present invention has the following flame retardant properties: flame burning time ≤ 3 seconds, flameless burning time ≤ 10 seconds. The oxygen index of the material is 30%. Antistatic performance: surface resistance < 1×10 6 Ω; It can fully meet the requirements of the Ministry of Coal Standards MT181-1988, MT 558.1-2005 and AQ1071-2009.

[0032] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.

Claims

1. A functional composite filler, characterized in that: The invention comprises the following raw materials in the following mass ratio: 16-20 parts of sodium montmorillonite; 3-8 parts of surfactant; and 2-6 parts of conductive filler.

2. A functional composite filler according to claim 1, characterized in that: The surfactant is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, dodecyltrimethylammonium bromide and dioctadecyldimethylammonium chloride, or a combination of two of them.

3. A functional composite filler according to claim 1, characterized in that: The conductive filler is one of special conductive carbon black, conductive graphite powder, carbon nanotubes or a combination of two thereof.

4. A method for preparing a functional composite filler according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Swelling sodium montmorillonite to obtain a montmorillonite suspension; adding a surfactant to the montmorillonite suspension, adding anhydrous ethanol, and then vigorously stirring at 60-80° C. for 1-3 hours; separating and drying to obtain modified montmorillonite; The particle size of the modified montmorillonite is in the range of 0.5 to 5 μm; the rotation speed of the violent stirring is in the range of 1000 to 1500 rpm / min; S2. Add the obtained modified montmorillonite and conductive filler into acetone, disperse them under ultrasonic conditions for 1-2 hours, fully dry and crush them to a product particle size range of 0.5-5 μm, and obtain a functional composite filler loaded with a conductive filler.

5. The method for preparing a functional composite filler according to claim 4, characterized in that: The swelling is performed by dispersing sodium montmorillonite in deionized water to obtain a suspension, and then fully stirring the suspension at room temperature to obtain swollen montmorillonite; the mass ratio of sodium montmorillonite to deionized water is 1 / 10-2 / 10, and the ratio of anhydrous ethanol to deionized water is 1 / 1-4 / 1.

6. A flame retardant and antistatic soft polyvinyl chloride composite material, characterized in that: The invention comprises the following raw material components in weight ratio: 90-120 parts of polyvinyl chloride; 1-5 parts of stabilizer; 50-65 parts of plasticizer; 1-5 parts of flame retardant; 1-5 parts of lubricant; 15-33 parts of the functional composite filler as described in any one of claims 1 to 3; and 0-3 parts of conductive filler.

7. The flame retardant and antistatic soft polyvinyl chloride composite material according to claim 6, characterized in that: The stabilizer is one or any combination of lead salt stabilizer, calcium stearate, lead stearate or rare earth composite stabilizer.

8. The flame retardant and antistatic soft polyvinyl chloride composite material according to claim 6, characterized in that: The plasticizer is one or any combination of dioctyl phthalate, dibutyl phthalate, dioctyl adipate or pentaerythritol oleate.

9. The flame retardant and antistatic soft polyvinyl chloride composite material according to claim 6, characterized in that: The lubricant is one or any combination of chlorinated polyethylene wax, paraffin, stearic acid or polyethylene wax; the flame retardant is one or any combination of antimony trioxide, antimony pentoxide and decabromodiphenyl ether.

10. The method for preparing a flame retardant and antistatic soft polyvinyl chloride composite material according to claim 6, characterized in that: The following steps are involved: S1. After weighing polyvinyl chloride, stabilizer, lubricant, flame retardant and functional composite filler according to weight, stir at high speed to mix thoroughly; when stirring until the material temperature reaches 86-90°C, add plasticizer, continue stirring at high speed until the material temperature reaches 100-120°C, and then switch to low-speed stirring; transfer the material to a mixer with cooling function, continue mixing and stirring at low temperature in the mixer, cool it to 40-60°C, and obtain a mixed material; the speed of the high-speed stirring is 1000-1500rpm / min; the speed of the low-speed stirring is 100-500rpm / min; S2. The mixed material obtained in S1 is extruded by a twin-screw extruder, and granulation is performed by traction air cooling, with the ratio of the discharge rate to the drawing rate being 1 / 1.5 to 1 / 3; the processing temperature of the twin-screw is controlled within the range of 130 to 170° C., and the granules are fully cooled to obtain a composite material.

Citation Information

Cited By

  • Environment-friendly wear-resistant electrostatic powder coating for medium-density fiberboard

    CN120118584A